The Impact of Compensation, Training &Development, and Organizational Culture on Job Satisfaction and employee Retention - Retno Sari Murtiningsih (Universitas Trisakti, 2020)
ABSTRACT The purpose of this study was to analyze the effect of compensation, training and development, and organizational culture on job satisfaction and employees retention. This study uses primary data in the form of questionnaires distributed and filled out by 150 respondents using a purposive sampling technique. As independent variables in this study are compensation, training and development, and organizational culture, while dependent variables are job satisfaction and employees retention. The job satisfaction variables also function as a mediation variable. To test the hypothesis SEM analysis is used. The results show that compensation and training & development have a positive effect on job satisfaction, while organizational culture doesn't have a positive impact on job satisfaction. Compensation has a positive impact on employees retention, but training & development, as well as organizational culture, do not have a positive effect on employees retention. Furthermore, job satisfaction has a positive impact on employees retention, and training & development has a positive impact on retention through job satisfaction. Keywords: compensation; training; development; organizational culture; job satisfaction; retention